Dimethyl Fumarate Blocks Tumor Necrosis Factor-Alpha-Driven Inflammation and Metabolic Rewiring in the Retinal Pigment Epithelium - Shu, Daisy Y.; Frank, Scott I.; Fitch, Tessa C.; Karg, Margarete M.; Butcher, Erik R.; Nnuji-John, Emmanuella; Kim, Leo A.; Saint-Geniez, Magali (Frontiers in Molecular Neuroscience, 2022)
The retinal pigment epithelium (RPE) acts as a metabolic gatekeeper between photoreceptors and the choroidal vasculature to maintain retinal function. RPE dysfunction is a key feature of age-related macular degeneration (AMD), the leading cause of blindness in developed countries. Inflammation is a key pathogenic mechanism in AMD and TNFα has been implicated as a pro-inflammatory cytokine involved in AMD. While mitochondrial dysfunction has been implicated in AMD pathogenesis, the interplay between inflammation and cellular metabolism remains elusive. The present study explores how the pro-inflammatory cytokine, tumor necrosis factor-alpha (TNFα), impacts mitochondrial morphology and metabolic function in RPE. Matured human primary RPE (H-RPE) were treated with TNFα (10 ng/ml) for up to 5 days. TNFα-induced upregulation of IL-6 secretion and inflammatory genes (IL-6, IL-8, MCP-1) was accompanied by increased oxidative phosphorylation (OXPHOS) and reduced glycolysis, leading to an increase in cellular ATP content. Transmission emission microscopy (TEM) revealed defects in mitochondrial morphology with engorged mitochondria and loss of cristae integrity following TNFα treatment. Pre-treatment with the anti-inflammatory drug, 80 μM dimethyl fumarate (DMFu), blocked TNFα-induced inflammatory activation of RPE (IL-6, IL-8, MCP-1, CFH, CFB, C3) and normalized their bioenergetic profile to control levels by regulating PFKFB3 and PKM2 gene expression. Furthermore, DMFu prevented TNFα-induced mitochondrial dysfunction and morphological anomalies. Thus, our results indicate that DMFu serves as a novel therapeutic avenue for combating inflammatory activation and metabolic dysfunction of RPE in AMD.